Spatial econometrics : qualitative and limited dependent variables - Fomby, Thomas B.; Escanciano, Juan Carlos; Hillebrand, Eric; Jeliazkov, Ivan, 1973-; Hill, R. Carter; Pace, R. Kelley; Baltagi, Badi H.; LeSage, James P. (Advances in econometrics ;, 2016)
Advances in Econometrics is a research annual whose editorial policy is to publish original research articles that contain enough details so that economists and econometricians who are not experts in the topics will find them accessible and useful in their research. Volume 37 exemplifies this focus by highlighting key research from new developments in econometrics.